ANALYSIS OF THE REASONS FOR THE PRACTICE OF PHYSICAL ACTIVITY FOR THE SENIOR CITIZEN (Fiep Bulletin - online, 2014)
In this project, we analyzed the reasons that take a senior citizen to practice exercise regularly.  For its concretion a composed sample of 30 participants of the CAC Serrano answered to a questionnaire that selected a series of reasons. Its lessons happened twice a week and each session had duration of 90 minutes. The aimed objectives were the improvement of flexibility, of the motor coordination, the balance and the cardio-respiratory capacity. The results had shown that the considered reasons more important are: to reduce the depression level of the participants for 93, 34%, to improve the physical conditioning and appearence (90, 01%), to improve the quality of life and health (86, 68%), Reduce anxiety (86, 68 %), to improve the mood (83, 35%) and reduce daily stress (80, 02 %).  To sum up, the importance of the practice of physical exercises for seniors has been ratified once more, and it shows it is also important to search for bigger knowledge about the aged public and their reasons for practicing physical activity.
Keywords: Aged; reasons for the practical one; physical activity